Gas-phase identification of (Z)-1, 2-ethenediol, a key prebiotic intermediate in the formose reaction. Issue 16 (4th February 2022) - Melosso, Mattia; Bizzocchi, Luca; Gazzeh, Houda; Tonolo, Francesca; Guillemin, Jean-Claude; Alessandrini, Silvia; Rivilla, Víctor M.; Dore, Luca; Barone, Vincenzo; Puzzarini, Cristina
Abstract : 1, 2-Ethenediol represents a key intermediate species in the process of sugar formation. Here, its rotational spectrum has been recorded and analyzed in order to enable its search in the interstellar medium. Abstract : Prebiotic sugars are thought to be formed on primitive Earth by the formose reaction. However, their formation is not fully understood and it is plausible that key intermediates could have formed in extraterrestrial environments and subsequently delivered on early Earth by cometary bodies. 1, 2-Ethenediol, the enol form of glycolaldehyde, represents a highly reactive intermediate of the formose reaction and is likely detectable in the interstellar medium. Here, we report the identification and first characterization of ( Z )-1, 2-ethenediol by means of rotational spectroscopy. The title compound has been produced in the gas phase by flash vacuum pyrolysis of bis- exo -5-norbornene-2, 3-diol at 750 °C, through a retro-Diels–Alder reaction. The spectral analysis was guided by high-level quantum-chemical calculations, which predicted spectroscopic parameters in very good agreement with the experiment. Our study provides accurate spectral data to be used for searches of ( Z )-1, 2-ethenediol in the interstellar space.